Application Requirements for E-management in Yemeni Ministry of Youth and Sports - Juaim, Hussein Salah; Ahmed, Kamal Ali (Journal of Educational and Psychological Sciences, 2023)
In spite of challenges that Yemeni ministry of youth and sports faces, it recognizes the importance of moving towards the E-management in it’s all operations Starting from the Ministry’s HQ and linking it to its various departments among, and working to find programs and applications that facilitate communication and connection to results positive outcomes to fulfill the aims that seeks for within transforming to E-management and warranties the reaction in between. The study aimed to identify the requirements for the application of E- management in Yemeni Ministry of Youth and Sports through ’informational electronic skills, Administrative and organizational skills in E- management, human resources and infrastructure and financial structures for electronic preparations , as well as identifying the differences in the requirements for applying E- management according to sex changes, age, educational qualification, years of experience, extent of knowledge of E- management, and used the descriptive approach to its suitability for the nature of the study, the study was conducted On a sample consisting of (92) employees, they were intentionally chosen, and the researchers have the results that the requirements for the application of E- management in Yemeni Ministry of Youth and Sports appeared in relative importance (54.15%) to a moderate degree as a whole, and this indicates an average reality of an application of institutional transformation towards E- management, the presence of statistically significant differences in the first dimension ’the reality of electronic skills and for the benefit of females, while there are no statistically significant differences in the rest of the dimensions of the requirements for the application of E- management attributed to the variable (sex), the presence of statistically significant differences in the dimensions of the requirements for the application of electronic management.’ Electronic, informational, administrative and organizational skills and financial resources are due to the (age) variable.